First Report of Pilidium concavum Causing Tan-brown Rot on Strawberry Nursery Stock in South Carolina - Fernández-Ortuño, D (Plant disease, 2014)
Pilidium concavum (Desm.) Höhn. [synanamorph: Hainesia lythri (Desm.) Höhn.] is an opportunistic pathogen that causes leaf spots and stem necrosis in a wide range of hosts, including strawberry (Fragaria ananassa) (1,2). In October 2013, 24 strawberry plug plants (cv. Chandler) with brown to dark brown necrotic lesions on stolons were obtained from a nursery in Easley, SC. The lesions were oval shaped and varied in length from 2 to 8 mm. The tips of stolons with larger spots had died. To isolate the causal agent, 3 to 5 cm of necrotic stolon tissue was surface disinfected for 1 min with 10% bleach, rinsed with sterile distilled water, air dried, and placed on potato dextrose agar (PDA). After 7 days of incubation at 22°C, pink-orange masses of spores emerged. Single spore colonies on PDA produced a gray to brown colony with whitish aerial mycelium. Numerous discoid to hemisphaerical conidiomata (0.3 to 2.2 mm in diameter) developed with a dark base and exuded a pink, slimy mass that contained many conidia. Conidiophores (10.2 to 47.8 × 0.8 to 2.0 μm) were hyaline, unicellular, cylindrical, and filiform. Conidia (3.0 to 8.5 × 1.0 to 2.9 μm) were aseptate, fusiform, hyaline, and canoe-shaped to allantoid. On the basis of morphology, the pathogen was identified as P. concavum (3). The internal transcribed spacer region ITS1-5.8S-ITS2 was amplified by PCR and sequenced with primers ITS1 and ITS4 (4). The sequence was submitted to GenBank (Accession No. KF911079) and showed 100% homology with sequences of P. concavum. Pathogenicity was examined on strawberry fruit and leaves. Our previous efforts to achieve infection without wounding failed, which is consistent with experiences of other scientists (not cited). Thus, 24 strawberry fruit were wounded (1 cm deep) with a needle once, and submerged for 3 min in a conidial suspension (2 × 106 conidia ml-1). Controls were wounded and submerged in sterile water. After 4 days of incubation at 22°C, characteristic symptoms were observed at the wound site only on inoculated fruit. Detached leaves (about 6 cm in diameter) from 3- to 4-week-old strawberry plants cv. Chandler were surface sterilized and placed right side up in petri dishes (one leaf per dish) containing water agar. Leaves were inoculated at one site with a 50 μl conidial suspension (2 × 106 conidia ml-1) after inflicting a scraping-type injury with a needle to the surface at the point of inoculation. Control leaves received just water. After 7 days of incubation at 22°C, only the inoculated leaves showed symptoms similar to those observed on strawberry stolons. The fungus was re-isolated from symptomatic fruit and leaf lesions and identity was confirmed based on morphological features. The experiments were repeated. To our knowledge, this is the first report of P. concavum causing tan-brown rot on strawberry tissue in South Carolina. Prior to this study, the pathogen has been described from different hosts and countries including Belgium, Brazil, China, France, Iran, Poland, and the United States. Contamination of strawberry nursery stock by P. concavum could become a plant health management issue in the United States, especially if the pathogen is transferred to strawberry production areas. Further information on in-field occurrence of P. concacum is needed. References: (1) J. Debode et al. Plant Dis. 95:1029, 2011. (2) W. L. Gen et al. Plant Dis. 96:1377, 2012. (3) A. Y. Rossman et al. Mycol. Prog. 3:275, 2004. (4) T. J. White et al. Page 315 in: PCR Protocols: A Guide to Methods and Applications. Academic Press, San Diego, CA, 1990